1979
DOI: 10.1037/0022-3514.37.10.1859
|View full text |Cite
|
Sign up to set email alerts
|

Reassertion and giving up: The interactive role of self-directed attention and outcome expectancy.

Abstract: Two experiments tested a theoretical model of behavioral self-regulation, which makes predictions about the effects of failure on a person's subsequent efforts. This model holds that degree of effort will be a product of two things: expectancy of being able to redress the failure and degree of self-attention. In the experiments, a failure pretreatment was used to create large within-self discrepancies among female subjects. It was predicted (a) that negative outcome expectancies regarding a subsequent task wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
163
2

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(178 citation statements)
references
References 34 publications
13
163
2
Order By: Relevance
“…We found evidence to suggest that coping is highly related to optimism and pessimism. Our findings, with an athletic population, support previous research that less optimistic individuals are more likely to withdraw or disengage (e.g., Carver et al, 1979;Solberg Nes, Segerstrom, and Sephton, 2005) and that more optimistic individuals use more approach coping strategies, but less avoidance strategies (Solberg Nes & Segerstrom, 2006). Seligman (1998) also suggested that optimism results in higher levels of achievement.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We found evidence to suggest that coping is highly related to optimism and pessimism. Our findings, with an athletic population, support previous research that less optimistic individuals are more likely to withdraw or disengage (e.g., Carver et al, 1979;Solberg Nes, Segerstrom, and Sephton, 2005) and that more optimistic individuals use more approach coping strategies, but less avoidance strategies (Solberg Nes & Segerstrom, 2006). Seligman (1998) also suggested that optimism results in higher levels of achievement.…”
Section: Discussionsupporting
confidence: 80%
“…Researchers became interested in studying optimism, because more optimistic individuals exhibit increased effort to achieve goals. Alternatively, less optimistic individuals are more likely to withdraw or disengage attempts at achieving a goal (e.g., Carver, Blaney, & Scheier, 1979;Gaudreau & Blondin, 2004;Solberg Nes, Segerstrom, & Sephton, 2005). In addition, optimism seems to be a predictor of sport performance.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that self-focus inhibits performance when outcome expectancies are low but facilitates performance when outcome expectancies are high (e.g., Brockner, 1979;Carver et al, 1979;Scheier & Carver, 1982). Therefore, if depressed people tend to self-focus after failures, when future outcome expectancies are likely to be low, their motivation and subsequent performance levels should be especially low.…”
Section: Consequences Of Self-focused Attent Ionmentioning
confidence: 99%
“…Moreover, depressed psychiatric patients report more negative affect when made selfaware by the presence of a mirror than depressed patients not made self-aware (Gibbons et al, 1985). Self-focus can heighten depressed mood by increasing the probability that an individual will make internal attributions for negative events (Fenigstein & Levine, 1984), by increasing negative expectancies about the future (Carver, Blaney, & Scheier, 1979;Pyszczynski, Holt, & Greenberg, 1987), and by interfering with performance on tasks (Fenigstein, 1979). Because the response styles theory holds that rumination consists of focus on one's symptoms of depression and repetitive thoughts about the possible causes and consequences of these symptoms, the results of these studies on self-awareness and depression are in line with the hypothesis that people who engage in rumination when depressed will remain depressed longer thanpeople who do not.…”
Section: Self-focus and Depressionmentioning
confidence: 99%